The amber spyglass - Pullman, Philip, 1946- (New York : Dell Yearling, 2003)
Lyra and Will find themselves at the center of a battle between the forces of the Authority and those gathered by Lyra's father, Lord Asriel.
Sequel to: The subtle knife.
Keywords: Belacqua, Lyra -- (Fictitious character) -- Fiction; Fantasy fiction, English; Missing persons -- Fiction; Fantasy; Arctic regions -- Fiction